ATURAN HUKUM ISLAM DALAM PENYELESAIAN KONFLIK TANAH SEMPADAN - Akbar, Ali (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2017)
Land problem can experienced by whole community. Increasing population, development and access of many people to obtain land as the basic capital of various interests, some times becomes a conflict. Conflict over lands are  actual issues that always comes up. One alternative solution to the land conflict is mediation. This mediation alternative has the characteristic that is short time, structurized, task orientation and a way of intervention involving various parties actively. The success of mediation is determined by the goddwill of both parties are in conflict to find an agreed way out. Mediation gives a sense of equalization so that the decision taken is without pressure. Keywords: Conflict, Land Border